Empowering Farmers through Fine Crumble Organic Fertilizer Innovation for Sustainable and Eco-Friendly Agriculture - Ariyadi, Bambang; Pastawan, Viagian; Prastowo, Joko; Nugraheni, Yudhi Ratna; Mubarokah, Wida Wahidah; Utomo, Budi; Awaludin, Aan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Munggang Wetan Hamlet, Sidoharjo Village, Samigaluh District, Kulon Progo, is in the Menoreh Highhills region, which has great goat farming potential. The KUBE Sejahtera X Binangun 005 farm group has been using goat manure as organic fertilizer; however, they continue to encounter challenges due to its rough texture and basic packaging. This community service activity aims to improve the quality of organic fertilizer products by applying Compost Maturation Technology and using a compost grinder to produce fine, crumbly organic fertilizer. The activity was conducted using a participatory approach that included outreach, training, technology application, and evaluation. The results of this community service activity showed a significant improvement in the physical quality of organic fertilizer that meets SNI standards, with characteristics such as a crumbly texture, blackish-brown color, a humus-like odor, and a temperature of 30–35°C, making it suitable for agricultural use. Additionally, the innovative packaging design has the potential to enhance the sales value of the partner group's organic fertilizer products. This activity not only supports local economic potential but also reinforces the principles of sustainable agriculture by utilizing livestock manure as a productive resource. This program is expected to become a model for rural community empowerment through appropriate, environmentally friendly technology.